Less is more: low expression of MT1-MMP is optimal to promote migration and tumourigenesis of breast cancer cells - Cepeda, Mario A.; Pelling, Jacob J. H.; Evered, Caitlin L.; Williams, Karla C.; Freedman, Zoey; Stan, Ioana; Willson, Jessica A.; Leong, Hon S.; Damjanovski, Sashko (Molecular cancer, 2016)
Background Membrane Type-1 Matrix Metalloproteinase (MT1-MMP) is a multifunctional protease implicated in metastatic progression ostensibly due to its ability to degrade extracellular matrix (ECM) components and allow migration of cells through the basement membrane. Despite in vitro studies demonstrating this principle, this knowledge has not translated into the use of MMP inhibitors (MMPi) as effective cancer therapeutics, or been corroborated by evidence of in vivo ECM degradation mediated by MT1-MMP, suggesting that our understanding of the role of MT1-MMP in cancer progression is incomplete. Methods MCF-7 and MDA-MB 231 breast cancer cell lines were created that stably overexpress different levels of MT1-MMP. Using 2D culture, we analyzed proMMP-2 activation (gelatin zymography), ECM degradation (fluorescent gelatin), ERK signaling (immunoblot), cell migration (transwell/scratch closure/time-lapse imaging), and viability (colorimetric substrate) to assess how different MT1-MMP levels affect these cellular parameters. We also utilized Matrigel 3D cell culture and avian embryos to examine how different levels of MT1-MMP expression affect morphological changes in 3D culture, and tumourigenecity and extravasation efficiency in vivo . Results In 2D culture, breast cancer cells expressing high levels of MT1-MMP were capable of widespread ECM degradation and TIMP-2-mediated proMMP-2 activation, but were not the most migratory. Instead, cells expressing low levels of MT1-MMP were the most migratory, and demonstrated increased viability and ERK activation. In 3D culture, MCF-7 breast cancer cells expressing low levels of MT1-MMP demonstrated an invasive protrusive phenotype, whereas cells expressing high levels of MT1-MMP demonstrated loss of colony structure and cell fragment release. Similarly, in vivo analysis demonstrated increased tumourigenecity and metastatic capability for cells expressing low levels of MT1-MMP , whereas cells expressing high levels were devoid of these qualities despite the production of functional MT1-MMP protein. Conclusions This study demonstrates that excessive ECM degradation mediated by high levels of MT1-MMP is not associated with cell migration and tumourigenesis, while low levels of MT1-MMP promote invasion and vascularization in vivo.